Optimising Maintenance: What are the expectations for Cyber Physical Systems - Jantunen, Erkki (2017)
Cyber Physical Systems Week 2016 (CPS Week 2016 Vienna). 11, Apr, 2016, 3rd International IFIP Workshop on Emerging Ideas and Trends in Engineering of Cyber-Physical Systems (EITEC’16),. Vienna, Austria.The 3rd International IFIP Workshop on Emerging Ideas and Trends in Engineering of Cyber-Physical Systems (EITEC’ 16) was held as part of CPS Week 2016 that took place in Vienna, Austria on April 11-14, 2016.